Qualitative changes of ocular surface in the patients with dry eye syndrome after Systein Ultra systemic using - T. I. Poltanova (Oftalʹmologiâ, 2014)
Purpose: To evaluate clinical efficiency of systemic usage of artificial tears drops Systein Ultra in the patients with different forms of dry eye syndrome.Methods: 42 patients (84 eyes) at the age of 21‑84 with different pathogenic forms of ocular xerosis and degrees of it’s severity were investigated. Systein Ultra eye drops in instillations were prescribed to all patients 3 times a day. Complex examination of being investigated was performed before the drug administration, in 7 days and then in 2 weeks.Results: Positive dynamics after the treatment was reavealed on average in 4‑7 days. There was decrease or absolute reduction of subjective and objective signs in the majority of cases. In the severest cases of the disease all investigated parameters were not changed.Conclusion: The positive clinical result after artificial tears drops Systein Ultra using, accompanied by eye comfort without significant side effects, allows us to recommend Systein Ultra to the wide application in therapy of different pathogenic forms dry eye syndrome.